A hybrid-flipped course in numerical methods for chemical engineers. (April 2023) - Lewin, Daniel R.; Barzilai, Abigail
Highlights: Hybrid 3-phased flipped classroom adopted to teach numerical methods. Learning analytics monitor students and classifies them by level of engagement. Active students perceived increased confidence by phase; passive students see none. Active students outperformed passive students in learning outcomes. Flipped class achieved good outcomes despite unusually heterogeneous student-mix. Abstract: In 2022, the numerical methods course taught at the Technion's Faculty of Chemical Engineering was transformed to hybrid-flipped format based on seven years of successful experience. This course involves three phases each week: (1) online pre-class preparation by students, (2) face-to-face class meeting with the instructor to introduce open-ended problem solving, and (3) an online active tutorial, where students solve problems for themselves. This paper describes the course learning objectives, content and format, data on students' engagement and perceptions, learning analytics tools used, and the summative outcomes assessment, as brought by the final exam results. The main conclusions are: (a) High-engaging students indicated that their confidence in mastery significantly improves with each phase, with the low-engagers indicating no significant improvement, and (b) High-engagers significantly outperformed low-engagers in learning outcomes: 86% of the students scoring over 90 were high-engagers, and 83% of the students who failed the exam were low-engagers.